Probiotic Lactobacillus sakei proBio-65 Extract Ameliorates the Severity of Imiquimod Induced Psoriasis-Like Skin Inflammation in a Mouse Model - Rather, Irfan A.; Bajpai, Vivek K.; Huh, Yun Suk; Han, Young-Kyu; Bhat, Eijaz A.; Lim, Jeongheui; Paek, Woon K.; Park, Yong-Ha (Frontiers in Microbiology, 2018)
This study was designed to evaluate the protective effect of ethanol extract (EEL1) isolated from a potent probiotic strain Lactobacillus sakei proBio-65 on imiquimod (IMQ)-induced psoriasis-like skin inflammation in a mouse model. Histopathological and histomorphometrical changes in the ear and dorsal skin tissues were observed under hematoxylin and eosin stain for general histopathological architectures or Masson’s trichrome stain for collagen fibers. The expression profile of psoriasis-associated specific genes was determined using Real-Time PCR analysis. As a result, topical application of IMQ resulted in a significant increase of mean total and epithelial (epidermis) thicknesses, the number of inflammatory cells infiltrated in the dermis, and the decrease of dermis collagen fiber occupied regions in the ear tissues of IMQ and IMQ plus vaseline treated groups when compared to the intact control group. A significant increase of epithelial thickness and number of inflammatory cells infiltrated in the dermis of dorsal skin tissues were also noticed in IMQ and IMQ plus vaseline treated groups as compared to the intact control group, suggesting classic IMQ-induced hypersensitive psoriasis. IMQ-induced hypersensitive psoriasis related histopathological changes to the ear and dorsal skin tissues were significantly inhibited by the treatment of a standard drug clobetasol and EEL1. Further, mRNA expression analysis indicated a significant increase in gene expression levels of pro-inflammatory cytokines, including IL-19, IL-17A and IL-23 in IMQ and IMQ plus vaseline treated groups than that of the control. Clobetasol and EEL1 treated groups resulted in a lower gene expression level of IL-19, IL-17A, and IL-23 as compared to IMQ and IMQ plus vaseline treated groups. These results enforce that EEL1 could be a novel treatment for psoriasis and an alternative to other drugs that pose a number of side effects on the skin.